Probiotic and prebiotic utilization in diets for free-range broiler chickens - Pelícia, K; Mendes, Aa [UNESP]; Saldanha, Espb; Pizzolante, Cc; Takahashi, Se; Garcia, Rg; Moreira, J; Paz, Icla; Quinteiro, Rr; Komiyama, Cm (Fundação APINCO de Ciência e Tecnologia Avícolas, 2004)
This work aimed to evaluate the effects of probiotic associated to prebiotic on performance, carcass and cut yields, qualitative traits of meat, development and score of lesions due to coccidiosis in digestive tract of broiler chickens raised in a free-range system during 85 days. One thousand, six hundred and ninety-six day-old male broiler chicks from naked-neck ISA S757-N Label Rouge line were used in a randomized block design with factorial scheme of 4x2 and four repetitions. The effect of four additive (1 - biologic promoter + coccidiosis vaccine; 2 - biologic promoter + anti-coccidiosis; 3 - chemical promoter + coccidiosis vaccine; 4 - chemical promoter + anti-coccidiosis) and two breeding systems from 35th day of age (one with no-access to pasture or confined and the other with free-access to pasture or semi-confined) on performance parameters, carcass and cut yields, qualitative meat traits, coccidiosis development and lesions in digestive tract were evaluated. There was effect (p<0.05) of additives only on sensorial analysis (meat quality) and percentage of large intestine. Breeding systems affected (p<0.05) live weight (LW) and LW gains, being the better results observed in semi-confined birds.
Keywords: Breeding system; growth promoter; intestine; Label Rouge; symbiotic